Hybrid Metaheuristics 10th International Workshop, HM 2016, Plymouth, UK, June 8-10, 2016, Proceedings - Blesa, Maria J.; Blum, Christian; Cangelosi, Angelo; Cutello, Vincenzo; Di Nuovo, Alessandro; Pavone, Mario; Talbi, El-Ghazali (Theoretical Computer Science and General Issues,, 2016)
This book constitutes the refereed proceedings of the 10th International Workshop on Hybrid Metaheuristics, HM 2016, held in Plymouth, UK, in June 2016. The 15 revised full papers presented were carefully reviewed and selected from 43 submissions. The selected papers are of interest for all the researchers working on integrating metaheuristics with other areas for solving both optimization and constraint satisfaction problems. They represent as well a sample of current research demonstrating how metaheuristics can be integrated with integer linear programming and other operational research techniques for tackling difficult and relevant problems.